Predictors of adherence of enhanced external counterpulsation in patients with coronary heart disease after discharge: A mixed-methods study - Yin, Yuhuan; He, Qinli; Zhang, Rong; Cheng, Hu; Zhang, Yiyin; Zhang, Juxia (Frontiers in Cardiovascular Medicine, 2022)
Background: Although enhanced external counter pulsation (EECP) has been included in the cardiac rehabilitation prescription for coronary heart disease (CHD) in China, because the total treatment duration of a course of EECP is 36-36h, the average hospital stay of CHD patients is short, and the adherence after discharge remains unclear. The purpose of this study is to investigate the adherence to EECP in CHD patients after discharge, and analyze the related influencing factors. Methods: A retrospective mixed method study combining qualitative and quantitative methods. Quantitative component included CHD patients who had received EECP treatment between March 2020 and August 2021. The qualitative component included in-depth interviews with patients who did not adhere to EECP after discharge. Binary Logistic regression was used to analyze the predictors of EECP adherence after discharge. In-depth interviews with patients were conducted to explore the reasons for dropping out of the EECP after discharge. Results: Among 1304 patients, only 24.23% adhered to EECP treatment after discharge. Binary logistic regression results showed that patients with disease duration less than 2 years (OR=3.13, 95%CI: 2.31-4.24), high school or below (OR=2.81, 95%CI: 1.98-4.01), distance between residence and hospital more than 20km (OR=2.08, 95%CI: 1.47-2.96), age more than 60 years (OR=2.00, 95%CI: 1.46-2.74), female (OR=1.64, 95%CI: 1.78-2.29), and angina pectoris (OR=1.65, 95%CI: 1.16-2.34) were more likely to not adhere to EECP treatment after discharge. However, patients with monthly family income over 8000¥ (OR=0.46, 95%CI: 0.28-0.75) were more likely to adhere to EECP treatment after discharge than those with household monthly income below 4000¥. In the qualitative results, the reasons why patients do not adhere to EECP after discharge mainly include insufficient understanding, restricted objective conditions and psychosocial factors. Conclusions: The adherence of CHD patients to EECP treatment after discharge was poor. It is necessary to develop effective intervention measures, such as brochures or videos to improve patients' understanding of the importance of adherence to EECP treatment after discharge. In addition, offering EECP treatment during off-hours and weekends may also improve adherence in more young patients.